Sebab Akibat Terganggunya Ekosistem Serangga sebagai Sumber Ide Penciptaan Karya Seni Lukis - Mu'minin, Muhammad Amirul; Syamsiar, Syamsiar (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
The author often hears complaints from the farmers about their declining agricultural yields and some even reached crop failure.  Factors that affect the decline in crop yields are various, such as plants that are attacked by planthoppers, changes in climate that occur  getting hotter, decreasing soil fertility. The purpose of this painting creation report is to describe the creation of the painting that has been created.  the foundation that  used in the creation of paintings using the opinion of Dick Hartoko  about art that refers to reality.  The statement then  created in a work of art with the visualization of a deformed shape stylized with decorative style.  The stage of creation refers to the opinion that  presented by L.H.  Chapman explains the stages of creating a work of art. First, find the initial idea.  Second, the refinement process,  development, and consolidation of these initial ideas.  Third, the stage of visualization into the media, namely how the artist  visualize into the medium.  The result of the creation of the final project  Includes, We're Friends  Not Opponent, Seeking Cover, Coexistence.